2022
DOI: 10.5115/acb.21.211
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and clinical relevance of the anatomical variations of suprarenal arteries: a review

Abstract: The suprarenal arteries are arising from three sources: superior suprarenal artery, middle suprarenal artery, and inferior suprarenal artery. Variations in the arterial supply of the suprarenal glands in respect to origin and number are quite common and very frequently reported. The most common variation noted is in the inferior suprarenal artery followed by the middle suprarenal artery and the least common variations were observed in the superior suprarenal artery. Arteriogram of the inferior suprarenal arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…15 Concomitant presence of an aberrant gonadal artery with variant suprarenal arteries and increased number of inferior suprarenal arteries, like in the present case, has been described in previous reports. 16 Kayalvizhi et al 17 in 2017 reported in their review that the incidence of 'arched testicular artery' or the 'arched gonadal artery of Luschka' ranges from 1.7% to 20.3%. The arched testicular artery observed here can be classified as type-III variety of the testicular artery, as per the Notkovich classification system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Concomitant presence of an aberrant gonadal artery with variant suprarenal arteries and increased number of inferior suprarenal arteries, like in the present case, has been described in previous reports. 16 Kayalvizhi et al 17 in 2017 reported in their review that the incidence of 'arched testicular artery' or the 'arched gonadal artery of Luschka' ranges from 1.7% to 20.3%. The arched testicular artery observed here can be classified as type-III variety of the testicular artery, as per the Notkovich classification system.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Concomitant presence of an aberrant gonadal artery with variant suprarenal arteries and increased number of inferior suprarenal arteries, like in the present case, has been described in previous reports. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Although it may be challenging to depict the adrenal blood vessels in ultrasmall dogs (less than 3 kg), further studies are needed because the number of cases of ultrasmall dogs is small in this study. In humans, adrenal arteries have also been reported to branch from gonadal, splenic and intercostal arteries (Priya et al, 2022 .). However, no branching from these arteries was reported in dogs before.…”
Section: Discussionmentioning
confidence: 99%
“…The blood supply of the adrenal glands comprises numerous branches from three types of arteries in humans: the superior adrenal artery, the middle superior adrenal artery and the inferior superior adrenal artery. A review on variations of these three types of adrenal arteries in humans has been published (Priya et al, 2022 ). In dogs, the adrenal glands are variously but always generously vascularized by small branches from the aorta, as well as the caudal phrenic, cranial abdominal, phrenicoabdominal, cranial mesenteric, celiac, renal and lumbar arteries (Hullinger, 2013 ; Singh, 2018 ).…”
Section: Introductionmentioning
confidence: 99%